The hermeneutic nature of analytic philosophy : a study of Ernst Tugendhat - Zabala, Santiago, 1975- (Columbia University Press, 2008)
Contemporary philosophers - analytic as well as continental - tend to feel uneasy about Ernst Tugendhat, who, though he positions himself in the analytic field, poses questions in the Heideggerian style. Tugendhat was one of Martin Heidegger's last pupils and his least obedient, pursuing a new and controversial critical technique. Tugendhat took Heidegger's destruction of Being as presence and developed it in analytic philosophy, more specifically in semantics. Only formal semantics, according to Tugendhat, could answer the questions left open by Heidegger. Yet in doing.